ANALISIS PENGARUH CITRA MEREK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN SIM CARD TELKOMSEL ( Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Katolik Santo Thomas Sumatera Utara ) - Manullang, Ida M (UNIKA Santo Thomas, 2017)
The purpose of this study to analyze the effect of brand image variables and customer satisfaction on customer loyalty Sim Card Telkomsel partially or simultaneously. Benefits of research, for the Academic. In addition to the literature and reference material for further research and for the Other Party. In addition to science and additional information on how to create customer loyalty. Number of samples of 60 respondents, method of data collection through questioner and documentation, method of data analysis with multiple regression The results of the first regression equation: LP = 3.503 + 0.246CM + 0.337KP This means that brand image and customer satisfaction have a positive influence on customer loyalty. The correlation coefficient (r) = .631. The coefficient of determination (r2) =. 398, meaning the variable of brand image and customer satisfaction able to explain equal to 39,8% while the rest equal to 60,2% explained by other variable outside this model. Based on the F test known the value of F = 15.672 significance 0.000